Inventing the Iceland Travel in 19th century : genesis, context and issues of a literary form - Mossé, Marie (HAL CCSD, 2022)
The recent literary form of the Iceland travel emerged during the 19th century, as a result of the (re)discovery of Iceland's material, cultural and literary resources by the countries of Western Europe and North America, a process that began in the previous century. First of all, the present thesis intends to propose an archaeology of the Iceland travel, situating its emergence at the crossroads of two factors: on the one hand, the intertextuality of travel literature as a whole, in which the Iceland travel reinvests the vast panel of representations of otherness; on the other hand, the secular history of the - essentially exogenous - representations of the North and of those who inhabit it, an unsurpassable legacy for the travellers to Iceland. The contradictory dimension of the Western imaginary of Iceland and the dynamic tensions that animate it will then invite us to question its influence, or even its reconduction on the level of the poetics of Iceland travel. To do so, we will propose the phenomenology of the Iceland travel in our research work. The Iceland travel as a literary form rose to prominence and gained its institutionalization in the context of the mutation of travel literature from the discursive model of the scholarly travelogue with encyclopaedic aims towards that of the romantic travel, a plural and plastic "mixed genre" (Philippe Antoine). But the Iceland travel is also characterised by two paradoxes. The first paradox is situated on the synchronic level: it is the collusion of textual patterns that are theoretically exclusive of each other, because they are respectively defined by antithetical networks of representations in the Western symbolic geography. The second paradox, situated on the diachronic level, lies in the discrete but certain existence of a nostalgic and anachronistic logic that leads to the choice by nineteenth-century travellers of formal paradigms that have become obsolete in the history of trave l literature. In the last part of our analysis, we will question the ...